Assessment of men involvement in family planning services use and associated factors in rural Ghana - Senanu Abigail Kpekpo Kwawukume; Alexander Suuk Laar; Tanko Abdulai (BMC, 2022)
Abstract Background In low-and-middle income countries (LMICs) less attention is paid to men's involvement in Family Planning (FP) programs where public health officials have advocated the involvement of men as a strategy for addressing the dismal performance of FP programs. The study assessed the involvement of men in FP use and the factors which promote or hinder the uptake of FP services among partners in a rural setting of northern Ghana. Methods A cross-sectional descriptive study was used to collect data from 200 respondents. Study respondents were selected through random cluster sampling. Results The findings showed that male partners' knowledge (95.5%) and approval (72.8%) of FP services were high. About 48% of men were involved in FP service utilization. Having living children (aOR; 1.71(1.27, 2.15)) and being knowledgeable (aOR; 6.14(1.38, 10.90)) about FP were positively associated men's involvement in FP service utilization. The findings also indicated that men had a higher propensity (X2 = 4.5534, p = 0.033) of supporting a FP method use. Women who reported that their spouse supported FP method use were more likely to use a contraceptive method (X2 = 9.5223, P = 0.002) if their spouse supported FP method use (X2 = 9.5223, P = 0.002) and if their partners had some education (X2 = 14.1133, P = 0.000). Reasons for low contraceptive use were health risks, side effects, and socio-cultural norms. Conclusion Family planning programs need to include men at all levels of health promotion and education of FP programs to help reduce misconceptions about contraceptive methods to increase acceptance and use among partners in rural settings of Ghana.